Título Padrão - Oddone, Maria Cristina (Arquivos de Ciências do Mar, 2021)
Carolus Maria Vooren was a teacher and researcher who worked at the Institute of Oceanography at the Universidade Federal do Rio Grande for 32 years. He worked in the area of Ecology, Biology and Population Dynamics of Chondrichthyan Fishes and Seabirds, being a pioneer in the studies of these two groups. He described three new species, a shark, Squatina occulta; a ray, Benthobatis stehmanii; and a chimera, Hydrolagus matallanasi. He also described an unprecedented form of embryonic development in the female’s body in species of angelshark, which he called cloacal gestation. He supervised hundreds of students, including scientific initiation, graduation, master and doctorate ones. His works and discoveries quickly gained international recognition, and are currently cited by the most respected members of the international academic community. He started a tireless fight for the conservation of chondrichthyans of South Brazil, to which he dedicated himself with much determination during the last years of his life. His studies on biology and ecology of sharks and rays were pioneering, not only in Brazil, but worldwide.